Traumatic Diaphragmatic Hernia: Diagnosis and Surgical Treatment in a Five-Month-Old Pup - Kumar, Amit; Pal Singh, Inder; Kumari, Ansu; Bhardwaz, Anavil; Saini, Gitesh (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The diaphragm serves as a muscular partition between thoracic and abdominal cavities that extends across the base of the thorax. The diaphragm plays a vital role during inspiration as its contraction causes the lungs to expand and fill with air. A diaphragmatic hernia (DH) is a condition in which rupture of the diaphragm allows abdominal organs to migrate into the pleural cavity. In companion animals, blunt trauma to the abdomen due to motor vehicle accidents is the common cause of traumatic DH (Hoddinott, 2013). Several other theories include an abrupt upsurge in the intraabdominal pressure following a powerful blow and failure of the glottis to remain closed, allowing the stabilizing effect of the air-filled lungs to be lost acutely (Hoddinott, 2013) or establishment of an acute and severe pressure gradient between the pleural and peritoneal cavities (Boudrieau, 1993) results in DH. The actual rupture or tear(s) occurs in the diaphragm which is least protected by the viscera at the time of injury.